A New Detailed Global Map of Lunar Light Plains - Barbara Giuri; Carolyn H. van der Bogert; Harald Hiesinger; Nico Schmedemann (The Planetary Science Journal)
Lunar light plains (LPs) are globally distributed, smooth and flat geologic units occurring in crater floors and topographic lows, similar in morphology to mare basalts, but with moderate to high albedo. Despite numerous studies investigating LPs, their emplacement mechanism(s), ages, and origins remain highly debated. To aid in deciphering their origin(s), we produced a new independent global map of the extent of the LPs. Thus, we (1) evaluated the morphological and compositional definitions of LP; (2) tested the reproducibility of previous work; and (3) extended the previously mapped extents of LPs. We find morphological similarities between near- and farside LPs with regional variations in albedo and FeO contents. We were able to reproduce the majority of previous LP maps, with some notable exceptions. We find ∼13% of the lunar surface is covered by LPs, which is slightly higher than previous studies, likely due to our inclusion of smaller deposits. Overall, the distribution of LPs on the nearside appears to be denser around mare regions and exhibits more widely varying degrees of smoothness, size, albedo, and FeO contents compared to the farside highlands. In contrast, on the farside, we find a large number of LPs with similar morphologies and FeO contents, in ray-like patterns likely related to the Orientale impact event. Beyond Orientale’s influence, the occurrences of LPs are of lower albedo and FeO contents are fewer and sparser, with similar morphologies to the nearside deposits. Thus, our study indicates that an impact-related origin for the majority of LP deposits is most likely.